Named Entities in the QTLeap Corpus of Online Helpdesk Interactions - Querido, Andreia (2016)
In this paper we present the annotation of a corpus with named entities that are classified into semantic types and disambiguated by linking them to their corresponding entry in the Portuguese DBpedia. This corpus, QTLeap Corpus, is a multilingual collection of question and answer pairs from a chat-based helpdesk service for Information and Communication Technologies. The resulting annotated corpus is a gold-standard named entity annotated lexical resource that is useful in supporting the training and evaluation of named entity annotation and disambiguation tools for Portuguese.